PENGARUH LIKUIDITAS, SOLVABILITAS, AKTIVITAS, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN DI BURSA EFEK INDONESIA - Sunarto Wage; Hariya Toni; Rahmat Rahmat (JURNAL AKUNTANSI BARELANG, 2022)
This study aims to examine and analyze the effect of liquidity, solvency, activity, and firm size on the profitability of companies listed on the Indonesia Stock Exchange for the 2016-2021. Profitability is proxied by ROA, liquidity is proxied by CR, solvency is proxied by DER, activity is proxied by Asset turnover, and company size is proxied by Ln (total assets). This study uses an associative quantitative approach with a causal nature. The population in this study are companies listed on the Indonesia Stock Exchange. There are 15 companies selected as samples using purposive sampling method. In this study, the analytical technique used is multiple linear regression analysis. Based on the results of simultaneous hypothesis testing, obtained a significant effect on profitability, with the results of the coefficient of determination test of 87%. Based on the results of partial hypothesis testing, liquidity, solvency, firm size affect profitability while activity has no effect on profitability.